The Nexus of Diet, Gut Microbiota and Inflammatory Bowel Diseases in Dogs - Soufien Rhimi; Aicha Kriaa; Vincent Mariaule; Amel Saidi; Amandine Drut; Amin Jablaoui; Nizar Akermi; Emmanuelle Maguin; Juan Hernandez; Moez Rhimi (Metabolites, 2022)
Canine inflammatory bowel diseases (IBD) are of increasing interest in veterinary medicine. They refer to complex and debilitating conditions of dogs’ gastrointestinal tract. Although little evidence for causal inferences is currently available, it is believed that IBD pathophysiology entails intricate interactions between environmental factors, the intestinal immune system, and the microbial communities that colonize the gut. To better understand the mechanisms underlying these disorders, leveraging factors associated with the development of these diseases is imperative. Of these factors, emerging evidence supports the role of dietary patterns as key players influencing the composition and function of gut microbes, with subsequent effects on health and disease. In this review, we particularly focus on addressing IBD in dogs and discuss how specific nutrients may elicit or relieve gut inflammation. Gaining mechanistic insights into such interplay and the underpinning mechanisms is key to inferring dietary recommendations, and setting up new and promising therapeutics.